Penurunan Derajat Kesehatan Pedagang Akibat Pajanan Debu PM10 di Kawasan Pasar Siteba Kota Padang - Gusti, Aria; Arlesia, Ayu; Anshari, Luthfil Hadi (Media Kesehatan Masyarakat Indonesia, 2018)
PM10 is a harmful dust that can cause various health problems, especially increased respiratory diseases. This study aims to determine the level of environmental health risk through the analysis of risk of PM10 exposure to traders in Siteba market area and risk management can be done. This research uses Environmental Health Risk Assessment (EHRA) method. The study was conducted from November 2016 to March 2017, with 45 respondents. The sampling technique is accidental sampling. Data analysis is univariate and EHRA. The average concentration of PM in the three sampling sites was 150 μm/Nm3. The reference concentration value (RfC) of PM10 is 0.014 mg/kg/day. The lifetime value of PM10 through inhalation at Kodam Intersection and Perumnas Intersection has a value of RQ>1, indicating that the exposure is not safe for traders so it is necessary to control and based on PM10 exposure of realtime intake through inhalation in the three sampling sites indicates that exposure is safe or not there is a risk to the trader with a RQ value <1. The results of the lifetime risk show that two sampling sites of Kodam Intersection and Perumnas Intersection have risks with RQ>1, which shows that traders are at risk of developing respiratory problems in the next 30 years.